The Exposed Infant - Delcourt, Marie (The Oedipus casebook, 2020)
In an earlier work I tried to show that Oedipus is one of those malefic newborn children whom ancient communities did away with because their deformity was a proof of divine wrath.¹ I did not sufficiently insist there on the fact that the exposed infants were emissary (or surrogate) victims. Their sacralization, in the event they were rescued, had the effect of bringing about a reversal of values, so that what had been seen as evil was now considered to be good. Similarly, a divine judgment, involving a trial from which the child emerges alive, ended not in an acquittal...